2018
DOI: 10.25092/baunfbed.390930
|View full text |Cite
|
Sign up to set email alerts
|

Determining qualification of urban signalized intersections with method of scoring design criteria

Abstract: Büyük kentler başta olmak üzere kentlerimizde, ulaşımın kilit noktaları olan kavşak alanlarında yaşanan zaman kayıpları ve kazalar, tüm karayolu kullanıcılarının yaşadığı olumsuzluklardır. Kavşaklardaki güvenlik eksiklikleri ve kapasite yetersizlikleri, ancak yapılacak olan düzenli ve etkin iyileştirme çalışmaları ile giderilebilecektir. Kavşak iyileştirme çalışmalarının yapılabilmesi için ilk önce kavşağın mevcut durumunun doğru ve eksiksiz olarak tespit edilmesi gereklidir. Konu ile ilgili literatür incelend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The effectiveness of the design was evaluated by considering different types of intersection phase plans and measured by considering the delay performance criterion. As a result of the analysis, as the left turn ratio increased, it was found that different alternatives should be preferred instead of roundabouts, depending on the increase in the number of phases [14]. A methodology is a method of gathering information and data to create works.…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of the design was evaluated by considering different types of intersection phase plans and measured by considering the delay performance criterion. As a result of the analysis, as the left turn ratio increased, it was found that different alternatives should be preferred instead of roundabouts, depending on the increase in the number of phases [14]. A methodology is a method of gathering information and data to create works.…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of the design was evaluated by considering different types of intersection phase plans and measured by considering the delay performance criterion. As a result of the analysis, as the left turn ratio increased, it was found that different alternatives should be preferred instead of roundabouts, depending on the increase in the number of phases [30].…”
Section: Methodsmentioning
confidence: 99%